Sex differences in clinical trials of ALRV5XR treatment of androgenetic alopecia and telogen effluvium - Feldman, Peter R.; Feldman, Oriel J.; Guevara-Aguirre, Jaime; Fiebig, Klaus M. (Frontiers in Medicine, 2022)
ALRV5XR treatment of androgenetic alopecia (AGA) and telogen effluvium (TE) has early evidence of regenerating a normal scalp hair phenotype in both sexes. Design: We performed two 24-week double-blind placebo-controlled comparison trials, one in each sex, on the ALRV5XR treatment effect on hair regeneration, in AGA and TE, in 92 AGA subjects (24 also had TE). Forty-six women (age 24-64 years) and 46 men (age 22–63 years) were randomized 1:1 to either ALRV5XR or placebo regimens (One bid oral capsule and daily administration of shampoo, conditioner, and follicle serum). Evaluation: Primary outcomes: Absolute and relative changes in terminal hair (TH) density. Secondary outcomes: Response rate, changes in vellus hair (VH) density, TH/VH ratio, hair diameter, growth, and shedding rate. Results: Forty-one women (20 ALRV5XR, 21 placebo) and 36 men (17 ALRV5XR, 19 placebo) completed the trials. TH outcome was evaluable for 18 and 21 women and 11 and 11 men (ALRV5XR, placebo, respectively). Efficacy in women: 30·1THs/cm2 (p=0·0002) and 19·7% (p=0·0016). Efficacy in men: 21·0 THs/cm2 (p=0·0014) and 16·4% (p=0·0012). 66·7% of women and 100% of men responded to ALRV5XR. TH/VH ratio for men increased 33·0% (p=0·0033). Growth rate in women increased by 30·7µm/24 hr (p<0·0001) and 10·0%(p<0·0001). There were no adverse events reported. Conclusions and Relevance: ALRV5XR induced significant regrowth of TH. Accelerating regrowth by reactivation of dormant telogen follicles were the dominant effects in women. Thickening of miniaturized hair and regrowth of dormant telogen follicles contributed equally to the increased TH seen in men. (See Abstract Figure).